MSME Development and Growth Strategy in Indonesia: Challenges and Opportunities in the Digital Economy Era - Nurul Aini (Proceeding of The International Conference on Business and Economics, 2024)
This study is focused on the development of small and medium enterprises (SMEs) growth in Indonesia. Various literature sources have been consulted to address the existing problems, and secondary data from relevant agencies such as BPS, BI, and the Ministry of Cooperatives and SMEs have been used. The challenges faced by SMEs in enhancing their business capabilities are multifaceted, encompassing several indicators. These include insufficient capital, both in terms of quantity and sources, inadequate managerial and operational skills in organizing, and limited marketing opportunities. Moreover, there is also unhealthy competition and economic pressures leading to a restricted and narrow business scope. It is crucial to address these concerns, especially in anticipation of Indonesia's participation in the ASEAN Economic Community (AEC) and the resulting open market. It is imperative for SMEs to enhance their competitiveness. However, these problems can be effectively tackled through various policies that facilitate easy access for SMEs to the banking industry. The fact that only 13.6% of credit growth is disbursed by the banking sector demonstrates that capital-related issues can be easily resolved, subsequently impacting management and enabling the production of more competitive products. By effectively addressing the challenges posed by the AEC, the government's concerns can be better addressed.